ASSESSMENT OF GROUNDWATER QUALITY AND ASSOCIATED HEALTH RISKS IN RURAL AREAS OF SINDH (PAKISTAN) - SARFRAZ, Muhammad; SULTANA, Nargis; ILYAS TARIQ, Muhammad (Studia Universitatis Babeș-Bolyai Chemia, 2018)
Groundwater quality has considerable impact on public health, especially in areas where majority of the people rely on groundwater for drinking purpose. In this scenario, investigation of 175 groundwater samples collected from district Jacobabad and Kashmor, Sindh Pakistan was carried out for physicochemical parameters (color, odor, taste, pH, EC, turbidity, alkalinity, hardness, Cl, SO4-2, NO3- and TDS), major cations (Na+, K+, Ca+2 and Mg+2), trace elements (F, As, Fe and Zn) and microbiological organisms (total coliform and faecal coliform). Analysis results showed high level of microbial contamination as 66 and 62% sampling sites were laden with total coliform and faecal coliform organisms respectively. On the other hand, chemicals constituents like hardness, Ca, Mg, Na, K, SO4, Cl, and TDS in 54, 72, 21, 47, 25, 73 and 49% water samples respectively were higher than GVs. Other than this, trace elements like F, Zn, As and Fe were also found in high concentration in 11, 04, 22 and 53% water samples respectively. Health risk assessment due to Fe, As and Zn revealed that arsenic HRI>1 in 22 and 13% water samples for children and adults respectively and overall CDIs and HRI were found in the order of As>Zn>Fe whereas, pollution index (Pi) for Fe was significant among all trace elements investigated.